The Relationship Between Confidence and Anxiety in Facing the Workforce Among Final-Semester Students - Patricia A. Chesser-Smyth; Ade Sukmawati; Jacinthe Dancot; Odeh Murad; Tananuraksakul , Noparat (Education Specialist, 2024)
This study aims to determine the relationship between self-confidence and anxiety in facing the world of work in final semester students at the Faculty of Technologies, South East Technological University. The method used in this study is the person correlation research method. Data collection techniques using the scale method. The self-confidence scale and anxiety scale in dealing with the world of work are measured using the Likert scale model. On the self-confidence scale, there are 40 items and on the anxiety scale in dealing with the world of work, there are 40 items. The reliability coefficient for the self-confidence scale is 0.447 and the reliability coefficient for the anxiety scale in facing the world of work is 0.408. To find out the relationship between self-confidence and anxiety in facing the world of work in final semester students, the Pearsion correlation technique was used. The results of this study's data analysis showed a significant value of the relationship between anxiety and self-confidence of 0.000 <0.05 which indicates that there is no relationship between self-confidence and anxiety. The result of obtaining the pearson correlation between the two variables is -0.002. This can be interpreted that the relationship between anxiety and self-confidence has a negative direction and is not significant. This means that the research hypothesis is accepted. In other words, there is a negative relationship between self-confidence and anxiety in facing the world of work in final semester students at the Faculty of Psychology, South East Technological University.